STUDI KASUS: ASUHAN KEBIDANAN DALAM MASA NIFAS DENGAN MASTITIS - Nova Linda Rambe; Melly Savira (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2022)
Back pain was a frequent complaint of expectant mothers who entered the age of trimester III. The complaint of back pain caused by the swelling of the uterus that causes muscle strain, and causes back pain. The purpose of this study is to administer obstetric care in pregnanat mothers with complaint of back pain through a cumulative approach to the varney bstetric management midwife. This Research used a case study to explore problems. The research subject was Mrs. N G1P0A0. The study was conducted in Mei 2021, in the Clinic Nana Diana Jl. Veteran, street.VIII Medan. Data collection techniques include primary data including physical examination, interviews, observation and secondary data, including documentation and literature study. Data analysis is done by making a narrative from the results of interviews and examinations using Varney's 7 steps. Midwifery care in the case of Mrs.